INTEGRITAS BUDAYA KERJA BIDANG BIMAS HINDU DENGAN PARISADA DALAM PEMBINAAN UMAT HINDU DI PROVINSI NUSA TENGGARA BARAT - I Ketut Nuasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
A Hindu integrity Guidance Division with Parisada as a tangible good work culture, will have an impact on Hindus who constitute the community auxiliaries. To improve the work culture takes time to change, then there is need for reform-reform that starts from the attitude and behavior as the leader of the institution Hindus. Likewise, each of the leaders of institutions of the people, both Hindu and Parisada Sector Guidance has have the duties and functions of each. Duties and functions of Sector Guidance Hindu Parisada in fostering, namely 1) carry out the services and guidance of Hindu society, 2) carry out the functions of the elaboration and implementation of technical policy in the guidance of the Hindu community, 3) will be maintained the integrity of the Hindu community to accommodate local cultural wisdom, and4) the realization of the Hindu community that qualified and capable srada and bhakti modern actualized.